The Sunday paper : a media history - Moore, Paul S., 1970-; Gabriele, Sandra, 1972- (University of Illinois Press, 2022)
"While the notion of leisurely sitting down with a paper over coffee seems almost quaint by now, the Sunday newspaper was once key to expanding circulation, increasing and expanding readerships. The weekend edition became essential in establishing the newspaper as actively involved in modernity and popular culture. In The Sunday Paper, Paul Moore and Sandra Gabriele trace the emergence of popular culture and mass media to the addition of the leisure reading supplements in weekend newspapers. They do so by tracking how newspapers borrowed from and collaborated with other media between 1888 and 1922--first magazines, later motion pictures, and radio--to transform news reading into media consumption. Under this single media form, North American journalism stewarded consumer society and found its own economic engine, appealing to mass readerships and mass market advertisers alike. Moore and Gabriele examine how the weekend edition maintained a readership commitment, participated in a continental media network, and circulated and animated the news. As readers became spectators and readerships audiences, the Sunday paper formed a visual medium that transformed journalism's written texts into a distinct, lively media supplement to weekday news. As the digitization of the news transforms the newspaper, this book explores the first time that newspapers were faced with multimedia competition and how they seem to anticipate the media world we are settling into in the age of the internet"-- Provided by publisher.
Keywords: American newspapers -- History -- 19th century.; American newspapers -- History -- 20h century.; American newspapers -- Social aspects.; Journaux américains -- Histoire -- 19e siècle.; Journaux américains -- Aspect social.; SOCIAL SCIENCE / General; American newspapers; American newspapers -- Social aspects; 1800-1999; History